Advanced Computational Methods for Knowledge Engineering Proceedings of the 5th International Conference on Computer Science, Applied Mathematics and Applications, ICCSAMA 2017 - Le, Nguyen-Thinh.; van Do, Tien.; Nguyen, Ngoc Thanh; Thi, Hoai An Le.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
These proceedings consist of 19 papers, which have been peer-reviewed by international program committee and selected for the 5th International Conference on Computer Science, Applied Mathematics and Applications (ICCSAMA 2017), which was held on June 30-July 1, 2017 in Berlin, Germany. The respective chapters discuss both theoretical and practical issues in connection with computational methods and optimization methods for knowledge engineering. The broad range of application areas discussed includes network computing, simulation, intelligent and adaptive e-learning, information retrieval, sentiment analysis, autonomous underwater vehicles, social media analysis, natural language processing, biomimetics in organizations, and cash management. In addition to pure content, the book offers many inspiring ideas and suggests new research directions, making it a valuable resource for graduate students, Ph.D. students, and researchers in Computer Science and Applied Mathematics alike.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence